Exploration of Increasing Students’ Critical Thinking in the Guided Discovery Learning Model on Light Waves - Syarifah Zahra; Iwan Permana Suwarna (Universitas Lambung Mangkurat, 2023)
This study explored increasing students' critical thinking in the guided discovery learning model on light waves at one of the high schools in South Tangerang City. The research design employed a quasi-experimental nonequivalent control group design with students from class XI IPA 3 as the experimental group and class XI IPA 5 as the control group. Data was collected using a pretest and posttest instrument comprising ten essay questions and was analyzed using the n-gain method. The N-gain analysis indicated a significant improvement in critical thinking skills, with a score of 0,60 for the experimental group and 0,25 for the control group. This study concludes that using the guided discovery learning model effectively enhances students' critical thinking skills in light waves at one of the high schools in South Tangerang City. The implications of this study indicate that implementing the guided discovery learning model in teaching light wave material is highly relevant for enhancing students' critical thinking abilities. This approach enables students to actively engage, analyze information, and solve problems, thereby fostering the development of their critical thinking skills. By acquiring critical thinking skills through guided discovery learning, students become better prepared to tackle complex challenges and support integrating critical thinking development into diverse subjects within the curriculum.